2014
DOI: 10.1038/nphys2932
|View full text |Cite
|
Sign up to set email alerts
|

Fast-cooling synchrotron radiation in a decaying magnetic field and γ-ray burst emission mechanism

Abstract: Synchrotron radiation of relativistic electrons is an important radiation mechanism in many astrophysical sources. In the sources where the synchrotron cooling timescale is shorter than the dynamical timescale, electrons are cooled down below the minimum injection energy. It has been believed that such 'fast cooling' electrons have a power-law distribution in energy with an index −2, and their synchrotron radiation has a photon spectral index 1 −1.5. On the other hand, in a transient expanding astrophysical so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
192
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(209 citation statements)
references
References 33 publications
11
192
0
1
Order By: Relevance
“…A marginally fast cooling regime (i.e. a situation where ν c ν m rather than ν c << ν m ) has been considered as a possible solution to the inconsistency between the expected and measured photon index (Derishev 2007;Daigne et al 2011;Beniamini & Piran 2013;Uhm & Zhang 2014). In the context of prompt emission, a theoretical prediction of the location of the cooling break frequency and of the ratio ν c /ν m is difficult to make, given the large uncertainties on the properties of the emitting region, such as dissipation radius, bulk Lorentz factor, magnetic field, and particle acceleration mechanism and efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A marginally fast cooling regime (i.e. a situation where ν c ν m rather than ν c << ν m ) has been considered as a possible solution to the inconsistency between the expected and measured photon index (Derishev 2007;Daigne et al 2011;Beniamini & Piran 2013;Uhm & Zhang 2014). In the context of prompt emission, a theoretical prediction of the location of the cooling break frequency and of the ratio ν c /ν m is difficult to make, given the large uncertainties on the properties of the emitting region, such as dissipation radius, bulk Lorentz factor, magnetic field, and particle acceleration mechanism and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Among the first class of models, we recall scenarios invoking Comptonization and/or thermal components Blinnikov et al 1999;Ghisellini & Celotti 1999;Lazzati et al 2000;Mészáros & Rees 2000;Stern & Poutanen 2004;Rees & Mészáros 2005;Ryde & Pe'er 2009;Guiriec et al 2011Guiriec et al , 2015aGuiriec et al ,b, 2016aGhirlanda et al 2013;Burgess et al 2014). For the second class of models (studies that consider synchrotron radiation) effects producing a hardening of the low-energy spectral index have been invoked, such as Klein-Nishina effects, marginally fast cooling regime, and anisotropic pitch angle distributions (Lloyd & Petrosian 2000;Derishev 2001Derishev , 2007Bosnjak et al 2009;Nakar et al 2009;Daigne et al 2011;Uhm & Zhang 2014). In spite of all theoretical efforts, there is still no consensus on the origin of the prompt emission.…”
Section: Introductionmentioning
confidence: 99%
“…As a last remark, we note that very recently Uhm & Zhang (2014) and Zhao et al (2014) showed that a very hard electron spectrum with p ∼ 1 can be produced in the fast-cooling regime due to synchrotron radiation in a strongly decaying magnetic field. This can explain the γ-ray burst (GRB) prompt emission spectra whose low-energy photon spectral index has a value ∼ 1.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This suggests us that the thermal emission plus the geometry effect can create the observed GRB spectra. Another remarkable model which can solve the α ∼ −1 problem is the fast cooling synchrotron radiation in the decaying magnetic field (Uhm & Zhang 2014). The low energy spectral slope α is found to be related to the decaying slope of the magnetic filed by an analytic method.…”
Section: Introductionmentioning
confidence: 99%